Pre-chiasmatic transection of the optic nerve can save contralateral vision in patients with optic nerve sheath meningioms - Zweckberger, Klaus; Unterberg, Andreas; Schick, Uta (Clinical neurology and neurosurgery, 2013)
Objectives - With respect to its characteristic pattern of growth from the orbit into the intracranial space toward the chiasm, patients with optic nerve sheath meningiomas (ONSM) are threatened to loose function of both optic nerves. Fortunately, in less than 5% both optic nerves are involved initially. Hence, prevention of vision of the contralateral eye is the foremost aim of any therapy. Performing pre-chiasmatic transection might offer a further treatment option to avoid further tumor growth toward the chiasm. - Patients and methods - In this retrospective study 12 patients with ONSM and blindness of the affected eye were included. The surgical approach was performed either from pterional intradural or as a combined approach from pterional extra- and intradural. - Results - Without any exceptions, vision of the contralateral eye could be preserved and did not show any deterioration after surgery or during the follow-up time of 50.6 months. Furthermore in 58.3% of patients gross total tumor resection could be achieved. During follow up observation in 67% of patients no further tumor progress or recurrences could be observed. 4 patients, however, showed delayed tumor progress or recurrences that were treated by radiotherapy. - Conclusion - Pre-chiasmatic transection of the optic nerve might offer a surgical treatment option to control tumor growth and to preserve vision of the contralateral eye.